SCALE FOR PRE-SERVICE SCIENCE TEACHERS’ KNOWLEDGE IN DESIGNING INCLUSIVE LEARNING: CONSTRUCTION, VALIDATION, AND RELIABILITY - Suprihatiningrum, Jamil; Wijayanti, Astuti; Salam, Firman Walidi; Hidayah, Muhammad Aditya (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Scale development is essential in testing constructs and variables in social research, including education. Scales that meet the rules of validity and reliability are developed using standardized procedures. This research focuses on scale production to create reliable and valid construct measures to assess teacher knowledge in designing inclusive learning, using three frameworks, namely Technological Pedagogical and Content Knowledge, Backward Design, and Universal Design for Learning. Research on this issue involves measuring organizational and psychological constructs, which present unique challenges because they are generally unobservable, very abstract, often complex, and may consist of several different components. As a result of this complexity, developing this scale was challenging. The production of this scale followed Boateng et al., and the field test involved 259 pre-service teachers. The Rasch Rating Scale Model analysis was used to test the scale and produced 18 items that have high reliability (0.96). This scale can be used nationally to assess teachers’ ability to implement inclusive education. The scale also applies as a teacher self-assessment tool for developing their competence.